Buda Factory, art centre, Kortrijk (OverHolland, 2017)
Design: 51N4EClient: City of Kortrijk / AGB Buda Program: artists’ studios, exhibition and event facilitiesSize: 4,240 m²Design period: 2005 (competition)2007 Construction period: 20102012